2015
DOI: 10.12968/ajmw.2015.9.1.17
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of midwives' practices to prevent peripartum sepsis in Zimbabwe

Abstract: This study investigated the availability of infection control policies and/or guidelines while observing midwives' practices in relation to peripartum sepsis prevention. A participant observational study collected data, in May and June 2014, by means of checklists from 37 purposively selected midwives working in the labour and postnatal wards of two central hospitals in Zimbabwe. Descriptive statistics and SPSS version 20 were used during data analysis. The results indicate lack of resources necessary for good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“… 23 In Zimbabwe, a study found that 62% of midwives never washed their hands before procedures. 24 HH definitions vary in these studies, making direct comparison with our results challenging. However, all studies highlight extremely poor HH behavior.…”
Section: Discussionmentioning
confidence: 74%
“… 23 In Zimbabwe, a study found that 62% of midwives never washed their hands before procedures. 24 HH definitions vary in these studies, making direct comparison with our results challenging. However, all studies highlight extremely poor HH behavior.…”
Section: Discussionmentioning
confidence: 74%
“…The prevalence of appropriate hand hygiene by HCW during labour and delivery has been found to be generally low [ 17 , 28 , 32 , 44 ]. This study finds that HCW maintain inadequate hand hygiene practices into the post-natal care period.…”
Section: Discussionmentioning
confidence: 99%
“…Many HCF-based studies on hand hygiene practices during maternal and newborn care in LMIC have focused on HCW hand hygiene during labour and delivery or high-risk environments such as the neonatal intensive care units [16][17][18][19][20]. Community-based studies have generally focused on caregiver hygiene practices for newborns who are born outside the health facility or during the late post-natal period (> 7 days after birth) [18,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of appropriate hand hygiene by HCW during labour and delivery has been found to be generally low (17,27,39,40). This study nds that HCW maintain inadequate hand hygiene practices into the post-natal care period.…”
Section: Discussionmentioning
confidence: 69%